Private company valuations by mutual funds - Vikas Agarwal; Brad M. Barber; Si Cheng; Allaudeen Hameed; Ayako Yasuda (University of Cologne, Centre for Financial Research (CFR), 2021)
Mutual funds value private security holdings at considerably different prices, update evaluations infrequently, and revise valuations dramatically at follow-on funding events. Predictable private valuation changes at follow-on rounds yield predictable fund returns, but effects are muted for large families, families with large investment in the private security, and families with large percentage stakes in funding rounds. Mutual funds with high exposure to private securities have outflows that are more sensitive to poor fund performance when the venture capital market also performs poorly. The results have welfare implications for retail investors interested in accessing private startups via investments in mutual funds.
Keywords: 330; Mutual funds; Venture capital; Private valuation; Stale prices; Financial fragility